Thymoquinone Inhibits Bone Metastasis of Breast Cancer Cells Through Abrogation of the CXCR4 Signaling Axis - Shanmugam, Muthu K.; Ahn, Kwang Seok; Hsu, Annie; Woo, Chern Chiuh; Yuan, Yi; Tan, Kwong Huat Benny; Chinnathambi, Arunachalam; Alahmadi, Tahani Awad; Alharbi, Sulaiman Ali; Koh, Angele Pei Fern; Arfuso, Frank; Huang, Ruby Yun-Ju; et al. (Frontiers in Pharmacology, 2018)
Overexpression of chemokine receptor type 4 (CXCR4) has been found to be associated with increased cell proliferation, metastasis and also act as an indicator of poor prognosis in patients with breast cancer. Therefore, new agents that can abrogate CXCR4 expression have potential against breast cancer metastasis. In this study, we examined the potential effect of thymoquinone (TQ), derived from the seeds of Nigella sativa, on the expression and regulation of CXCR4 in breast cancer cells. TQ was found to inhibit the expression of CXCR4 in MDA-MB-231 triple negative breast cancer (TNBC) cells in a dose- and time-dependent manner. It was noted that suppression of CXCR4 by TQ was possibly transcriptionally regulated, as treatment with this drug caused down-regulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-B) activation and suppression of NF-κB binding to the CXCR4 promoter. Pretreatment with a proteasome inhibitor and/or lysosomal stabilization did not affect TQ induced suppression of CXCR4. Down-regulation of CXCR4 was further correlated with the inhibition of CXCL12-mediated migration and invasion of MDA-MB-231 cells. Interestingly, it was observed that the deletion of p65 could reverse the observed anti-invasive/anti-migratory effects of TQ in breast cancer cells. TQ also dose-dependently inhibited MDA-MB-231 tumor growth and tumor vascularity in a chick chorioallantoic membrane assay model. We also observed TQ (2 mg/kg and 4 mg/kg) treatment significantly suppressed multiple lung, brain, and bone metastases in a dose-dependent manner in a metastasis breast cancer mouse model. Interestingly, H&E and immunohistochemical analysis of bone isolated from TQ treated mice indicated a reduction in number of osteolytic lesions and the expression of metastatic biomarkers. In conclusion, the results indicate that TQ primarily exerts its anti-metastatic effects by down-regulation of NF-B regulated CXCR4 expression and thus has potential for the treatment of breast cancer.